1991
DOI: 10.1079/bjn19910062
|View full text |Cite
|
Sign up to set email alerts
|

Rat small intestinal morphology and tissue regulatory peptides: effects of high dietary fat

Abstract: Sprague-Dawley rats (3 weeks old) were fed on isoenergetic diets in which 40% of the total energy was provided as fat either in the form of butter (high saturated fat), olive oil (high monounsaturated fat) or maize oil (high polyunsaturated fat), with one group on low-fat (10% of total energy) standard diet as a control. Animals were killed after 8.4 (se 0.8) weeks by cardiac puncture. Similar pieces of jejunum and ileum were prepared for morphometric studies. Extracts of tissue from the proximal and distal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
2

Year Published

1991
1991
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 26 publications
3
25
0
2
Order By: Relevance
“…In our experimental model, mice chronically fed a HFD showed changes in some morphometric parameters, consistent with the results of the previous studies (Sagher et al 1991, Thomson et al 1996, Scoaris et al 2010, De Barros Alencar et al 2012, which were similar in duodenal and jejunal segments. Indeed, we cannot establish whether the effects observed are specifically induced by the fat or by the different caloric intake.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our experimental model, mice chronically fed a HFD showed changes in some morphometric parameters, consistent with the results of the previous studies (Sagher et al 1991, Thomson et al 1996, Scoaris et al 2010, De Barros Alencar et al 2012, which were similar in duodenal and jejunal segments. Indeed, we cannot establish whether the effects observed are specifically induced by the fat or by the different caloric intake.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, morphological alterations of rat small intestine including hypertrophy, increase in the villus height, and increase in the number of enterocytes per villus have been observed in response to dietary fat adaptation (Sagher et al 1991, Thomson et al 1996. However, a potential role of GLP2 in mediating the mucosal responses to a HFD has not been considered yet.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that rats fed a diet high in polyunsaturated fat had both the tallest villi [17] and the best absorp tion [ 18]. The ileal absorptive cells of the mice fed the pectin diet contained numerous perox isomes, whereas there were few in the same cells of those fed the cellulose diet.…”
Section: Discussionmentioning
confidence: 98%
“…In rats, exposure to a high-fat diet for 1 (16), 2 (18), or 8 (17) wk increases intestinal villus height (17) and pancreatic lipase secretion (17,18). A high-fat diet also attenuates the inhibition of gastric emptying and food intake in response to the intraduodenal administration of fat (10 -12).…”
Section: Introductionmentioning
confidence: 99%